Evaluation of Saccharomyces cerevisiae as an antiaflatoxicogenic agent in broiler feedstuffs - Pizzolitto, Romina Paola (2013)
Aflatoxins (AFs) are the most important mycotoxins produced by toxigenic strains of various Aspergillus spp. Biological decontamination of mycotoxins using microorganisms is one of the well-known strategies for the management of mycotoxins in feeds. Saccharomyces cerevisiae strains have been reported to bind aflatoxin B1 (AFB1). The aim of this study was to evaluate the ability of S. cerevisiae CECT 1891 in counteracting the deleterious effects of AFB1 in broiler chicks. The experimental aflatoxicosis was induced in 6-d-old broilers by feeding them with 1.2 mg AFB1/kg feed for 3 weeks and the yeast strain was administrated in feed (1010 cells/kg), in the drinking water (5 x 109 cells/L) or a combination of both treatments. A total of 160 chicks were randomly divided into 8 treatments (4 repetitions per treatment). Growth performance was measured weekly from d 7 to 28 and serum biochemical parameters, weights and histopathological examination of livers were determined at d 28. AFB1 significantly decreased the body weight gain, feed intake, and impaired feed conversion rate. Moreover, AFB1 treatment decreased serum protein concentration and increased liver damage. The addition of S. cerevisiae strain to drinking water, to diet contaminated with AFB1, showed a positive protection effect on the relative weight of the liver, histopathology and biochemical parameters. Furthermore, dietary addition of the yeast strain to drinking water alleviated the negative effects of AFB1 on growth performance parameters. In conclusion, this study suggests that in AFB1 contaminated feed the use of S. cerevisiae is an alternative method to reduce the adverse effects of aflatoxicosis. Thus, apart from its excellent nutritional value, yeast can also be used as mycotoxin adsorbents.